New insights into the role of cellular senescence and rheumatic diseases - Wen, Jianting; Liu, Jian; Wan, Lei; Wang, Fanfan (Frontiers in Immunology, 2025)
Rheumatic disease is a chronic inflammatory disease that imposes significant societal and economic burdens. Accumulating evidence has demonstrated that cellular senescence plays an important role in inflammation-induced rheumatic diseases. Due to the lack of effective therapies, there is an urgent need for a deeper understanding of the etiopathogenesis of rheumatic diseases. In this review, we systematically summarized the role of cellular senescence in rheumatic diseases. We first focused on the mechanisms and hallmarks of cellular senescence, and then summarized evidence that can induce or aggravate cellular senescence, as well as related signaling pathways. Next, we discussed the mechanisms of interaction between cellular senescence and rheumatic diseases. Additionally, we focused on and elucidated the mechanisms and impacts of chondrocyte senescence and mesenchymal stem cell (MSC) senescence in osteoarthritis (OA) and systemic lupus erythematosus (SLE), respectively. Finally, we highlighted the potential of therapies targeting senescent cells in rheumatic diseases as a strategy, especially the multi-target effect of traditional Chinese medicine.